Effect of long-acting injectable antipsychotics on antipsychotic dose changes in patients with schizophrenia - Tatsunori Suzuki; Keita Okinaga; Tomoe Abe; Mariko Kawai; Michiru Ochiai; Ryozo Enomoto; Takeo Yanagawa; Kazuki Aida; Shunsuke Hayasaka (Journal of Pharmaceutical Health Care and Sciences, 2026)
Abstract Background Long-acting injectable (LAI) antipsychotics are commonly used to address poor adherence. However, their effects on prescribed oral doses remain unclear. This study investigated LAI-related changes in antipsychotic dose. Methods This retrospective study included 33 Japanese patients with schizophrenia who began treatment with one of the following LAIs: risperidone long-acting injection biweekly (RLAI), paliperidone palmitate long-acting injection monthly (PP), or aripiprazole hydrate prolonged release injection monthly (AOM). Prescribed drugs and doses were recorded at seven time points, from 4 weeks before to 24 weeks after LAI initiation. Doses were converted to chlorpromazine (CP) equivalents, and dose changes were assessed. Effects of disorder duration and age at LAI initiation were also evaluated. Results After LAI initiation, significant dose increases were observed in PP- and AOM-treated patients but not in those receiving RLAI. In AOM-treated patients, %CP changes varied by initial dose, with dose maintenance at < 400 mg and decreases at 400–800 mg and ≥ 800 mg. A significant effect of initial dose, number of concomitant antipsychotics, and disorder duration before LAI initiation was also found ( p < 0.05). Conclusions These findings underscore the importance of follow-up and dose reassessment after starting LAI treatment.